Triazolam, obesity and non cardiac pulmonary edema - Fabio Di Stefano; Salvatore Nicolai; Filippo Salvati (Italian Journal of Medicine, 2012)
Introduction Triazolam belongs to the group of benzodiazepines and may have side effects on the respiratory system which include not only respiratory depression, but also transient benign non cardiac pulmonary edema. Case report A 52 year old obese woman developed pulmonary edema after she was taking triazolam for almost two weeks without any other medications. All possible cardiogenic and non cardiogenic causes were excluded. The condition was severe enough to require non invasive ventilation. Discussion This case differs from the other report of triazolam associated non cardiac pulmonary edema for its severity requiring non invasive ventilation. The pathogenetic mechanism is unknown. Despite the lack of objective evidence to explain pulmonary venous hypertensive changes in our case, we want to advice that triazolam should be used with caution in obese patients, as obesity might aggravate this described drug adverse reaction.